Silicon carbide power devices in multi-port active bridge converter for shipboard micro-grid applications - Wang, Zhenyu (2019)
Due to the increasing demand of shipboard micro-grids in high efficiency and high-power density, the conventional Si based power devices have been limited due to the limited material properties to achieve higher switching frequency or higher efficiency. As the next-generation power devices, SiC based power devices are the ideal alternative to replace conventional Si devices with increased efficiency and power density. On the other hand, the SST concept is proposed to replace conventional line frequency transformers in shipboard micro-grids without compromising the capability of galvanic isolation and voltage matching, but the volume and weight could be reduced significantly. As the core circuit of SST, the DAB converter and three-port version becomes attractive, and the currently commercialised SiC-MOSFET power module provides the enabling solution of DAB converter to be pushed to higher switching frequency, which hence increases the power density with acceptable efficiency.